Handling Community Social Conflict Through Restorative Justice in East Bintan Police Station - Karim, Zamzami A; Usman, Nurbaiti; Prastiyo, Endri Bagus; Oktaviani, Indah; Wibowo , Dimas (Pencerah, 2024)
The purpose of this study was to determine the Handling of Social Conflict in the Community Through Restorative Justice (Restorative Justice) at the East Bintan Police. In this study, the sample consisted of 3 police officers from the East Bintan Police and 5 people from East Bintan who had undergone Restorative Justice. The sample in this study was 5 people. The data analysis technique used in this study was a qualitative descriptive data analysis technique. Based on the results of the study, it can be concluded that the Handling of Social Conflict in the Community Through Restorative Justice at the East Bintan Police has been running well, this can be seen from the police conducting investigations to collect evidence and information related to the reported cases, bringing in witnesses, listening to both parties. The police of course seek the best solution, especially in social cases that exist in the community. There are at least three focuses of restorative justice. First, repairing losses caused by crime by involving victims. Second, seeing the perpetrator's accountability. Finally, preventing similar losses in the future. Then there is a deliberation, Actually Restorative Justice is a method, not a form of decision on crimes as a resolution to solving problems by improving the situation or losses for victims. The principle of Restorative Justice is to restore good relations between the perpetrator and the victim, by paying attention to the victim's suffering.